Utilization of Multi-Sensory Approaches in Teaching Reading and Performance Among Pupils - Mia O. Reduca; Wenie L. Nahial (Future Science / FSH-PH Publications, 2026)
Reading problem has been noted every year, particularly among pupils in Key Stage 1. These pupils are expected to know how to read upon passing the first stage in basic education. On this conjecture, the study aimed to determine the utilization of multisensory approaches in teaching reading among the 35 teachers of Grades 1 to 3. A quantitative descriptive research design was employed, utilizing a survey questionnaire as the primary data collection tool with a casual interview to verify responses. By checking the assumptions of a parametric test, the identification of an appropriate statistical test was observed to produce reliable results. The majority of the respondents were in the middle adulthood stage, predominantly females, who had gained sufficient experience by serving for at least 11 years, attending 3 to 5 related trainings, and having earned at least units in a master’s degree program. The perception of the respondents in the multisensory approach was at a high extent, indicating the utilization of the intervention at all times, while the academic performance of the pupils plateaued at a satisfactory level. The calculation further showed that there was an extremely weak or negligible association between the extent of multisensory approach utilization and pupils’ academic performance. Moreover, the extent of utilization of a multisensory approach did not differ among the respondents when grouped by age, sex, number of years in teaching, highest educational attainment, and school size.